2013
DOI: 10.1002/cctc.201300718
|View full text |Cite
|
Sign up to set email alerts
|

Porous Cobalt Titanate Nanorod: A New Candidate for Visible Light‐Driven Photocatalytic Water Oxidation

Abstract: New narrow band gap semiconductor cobalt titanate (CoTiO3) nanorods are fabricated via an ethylene glycol‐mediated route and further calcination in air. The glycolate precursors and porous CoTiO3 nanorods are investigated in detail by using SEM, TEM, XRD, thermogravimetric, FTIR, and UV/Vis spectroscopy and N2 adsorption–desorption isotherm. The effect of calcining temperature is also studied, and 700 °C is found to be the optimal calcining temperature used to prepare porous CoTiO3 nanorods with high crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
61
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 35 publications
9
61
2
Order By: Relevance
“…14,15 In this sense, several types of structures with earth-abundant elements in the transition metal position (B) such as LaNiO 3 catalyst, and the latter has been evaluated as electrocatalyst for the methanol oxidation reaction. [16][17][18] These materials, however, at difference to other titanates such as SrTiO 3 display lower band gap values, making them more suitable for the O 2 evolution half-reaction under solar light, for instance in systems involving Z-Scheme configurations or as photoanodes in PEC approaches.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In this sense, several types of structures with earth-abundant elements in the transition metal position (B) such as LaNiO 3 catalyst, and the latter has been evaluated as electrocatalyst for the methanol oxidation reaction. [16][17][18] These materials, however, at difference to other titanates such as SrTiO 3 display lower band gap values, making them more suitable for the O 2 evolution half-reaction under solar light, for instance in systems involving Z-Scheme configurations or as photoanodes in PEC approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that nanostructured cobalt titanate with abundant pores exhibits an improved gas sensing performance as compared with the nanocrystalline CoTiO 3 . Several investigators have reported on the specific synthesis approaches of porous cobalt titanate such as electrospinning method [23], ethylene glycol-mediated method [24], template method [25], and sol-gel method [26]. However, less attention has been paid to the effect of pore size distribution on the gas sensing performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, their activities for drugs degradation are not sufficient yet at wavelengths longer than 500 nm. Recently, special attention has been paid to the titanium -based ilmenites, MTiO3, as chemical, electrical and optical materials because of their excellent ferroelectric, dielectric and electro-optical properties [19][20][21]. Nickel titanate (NiTiO3) belongs to the ilmenite type structure with both Ni and Ti possessing octahedral coordination and the alternating cation layers occupied by Ni +2 and Ti +4 alone.…”
Section: Introductionmentioning
confidence: 99%